2023
DOI: 10.1002/ajcp.12695
|View full text |Cite
|
Sign up to set email alerts
|

Seeking utopia: Psychologies' waves toward decoloniality

Abstract: This paper provides a review of empirical studies published with a decolonial epistemic approach in psychology. Our goal was to better understand how decolonial approaches are being practiced empirically in psychology, with an emphasis on community‐social psychology. We first discuss the context of colonization and coloniality in the research process as orienting information. We identified 17 peer‐reviewed empirical articles with a decolonial approach to psychology scholarship and discerned four waves that cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Qualitative inquiry can serve to recenter marginalized epistemology. For instance, Rodriguez Ramirez and Langhout (2023) reviewed 17 empirical studies with ontological and epistemological studies that aimed to unsettle coloniality. From this qualitative review, they highlighted participatory ontoepistemologies as supporting a decolonial turn.…”
Section: Recommendations For Transformative Futuritymentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative inquiry can serve to recenter marginalized epistemology. For instance, Rodriguez Ramirez and Langhout (2023) reviewed 17 empirical studies with ontological and epistemological studies that aimed to unsettle coloniality. From this qualitative review, they highlighted participatory ontoepistemologies as supporting a decolonial turn.…”
Section: Recommendations For Transformative Futuritymentioning
confidence: 99%
“…Several paradigmatic shifts may be harnessed toward transformation. In their recent review, Rodriguez Ramirez and Langhout (2023) also identified that researchers are “embracing a decolonial turn” in the psychological sciences (p. 6). As we write, Thema Bryant, the current president of the APA has convened a committee to make progress on one of her five presidential initiatives “decolonizing and liberation psychology dissemination.” Relatedly, there are two active calls for article submissions to the American Psychologist related to practicing decolonial and liberation psychologies and on recentering global marginalized knowledges toward decolonial psychology, respectively.…”
Section: Recommendations For Transformative Futuritymentioning
confidence: 99%